THE ANALYSIS OF THE RELATIONSHIP BETWEEN EXTRINSIC AND INTRINSIC MOTIVATION WITH EXCLUSIVE BREASTFEEDING IN INFANTS 0-6 MONTHS OF AGE AT THE RANGKASBITUNG HEALTH CENTRE AREA, LEBAK REGENCY, BANTEN PROVINCE IN 2023 - Juwita, Erna Triana; Sugiatini, Titin Eka (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Based on the preliminary study on the respondents of the Rangkasbitung Community Health Centre Area, Lebak-Banten Regency, it was found that mothers who did not carry out exclusive breastfeeding were caused by various factors, including the small amount of breast milk produced by the mother or even not coming out. Other causes are working mothers and external factors that influence them such as stress (deep thoughts) experienced by new mothers. The purpose of this study was to determine the frequency distribution of extrinsic and extrinsic motivation in exclusive breastfeeding for infants aged 0-6 months in the Rangkasbitung Health Centre Area, Lebak-Banten Regency. The method used in this study was a descriptive analytic survey method with a cross-sectional study design. The research sample was 21 respondents consisting of breastfeeding mothers and infants aged > 6 months to 24 months who came to Posyandu Teratai 13 which is located at Kp. Selahaur, Cijorolebak Village, Rangkasbitung District, Lebak-Banten Regency. The results showed that there was a relationship between extrinsic motivation (p value of 0.004) and intrinsic motivation (p value of 0.001) with exclusive breastfeeding in infants aged 0-6 months in the Rangkasbitung Health Centre Area, Lebak-Banten Regency. The value of extrinsic motivation of respondents was mostly in the high category, namely 11 respondents (52.4%), the value of intrinsic motivation of respondents was mostly in the high category, namely 13 respondents (61.9%) and most of them provided exclusive breastfeeding, namely 15 respondents (71.4%) out of a total of 21 respondents.